Female autonomy and rural tourism in Tzibanzá, Cadereyta de Montes, Querétaro, Mexico - Ilithya Guevara Hernández (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
One of the elements that are disrupted by development is gender roles. These changes are not always negative, and the objective is to identify whether the participation of women in the fishing cooperative and the tourism project of La Isla makes it possible to build autonomy. Ever since the 90s, the Tzibanzá village has been the target of a series of development projects that have included or excluded them in decision-making. However, every project impacted the organization and productive activities and their daily life. Results of an investigation still in progress are presented, which start from the qualitative approach combining quantitative information-gathering techniques: a questionnaire to cooperative members and not cooperative members; and qualitative: non-participant observation, qualitative interviews, and focus groups. The tourism production and project cooperative have operated for just over 20 years with relative success in income, job creation, and participation. Women have been incorporated not necessarily by their own decision, but in their husbands' absence due to migration or the position was inherited. However, participating in activities considered "masculine" leads them to reconsider their role in the community and family, enabling decision-making to previously had no access. Autonomy indeed needs social recognition to be exercised; however, we consider that joining actively and as protagonists in productive activities allows progress.